Association between craneocervical posture and maloclusions. A review - Ramírez Velásquez, Mariela (2021)
The biomechanical relationship between the cranio-cervical segment and alterations in the form  and  function of the stomatognathic system has been a highly controversial topic, due to its influence on numerous and different aspects with which it is linked, such as respiratory function, temporomandibular joint dysfunctions, or maxillomandibula relationships. The objective of this study was to determine the association between the alterations of the cervical cranial posture and the malocclusions, by means of a bibliographic review using as strategies, the search in the databases PubMed (Medline), SciELO; Redalyc, LILACS; articles between 2015-2019 published in English, Spanish and/or Portuguese were included. A total of 445  publications  were  obtained, 427 were excluded after the evaluation of titles and abstracts, leaving 18 articles for reading and analysis, finally resulting in 8 articles included in this study. It was determined that there is little scientific evidence with appropriate designs to determine an association between the biomechanical relationship of the head, cervical spine and teeth, in addition there is evidence of lack of homogeneity between the measurements that determine the alterations of the cranio-cervical segment in the different studies.